2016
DOI: 10.15171/jcvtr.2016.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ventolin on QTc in children with respiratory distress

Abstract: Introduction: β2–agonists are first election drugs for the treatment of respiratory disease that may alter cardiac autonomic modulation. The aim of this study was to evaluate the effects of nebulized Ventolin on electrocardiogram, particularly QTc interval to assess the potential arrhythmogenic risks. Methods: A total of 192 patients between 2 months and 15 years which received nebulized Ventolin were enrolled in this study. Patients were divided into two groups. Electrocardiograms of patients before and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Out of the 42 potential DDIs found, most of them had moderate (80.95%) and minor (73.80%) severity that is sufficiently to warn us to have a monitoring for the potential dangerous, as shown in Figure 1. (Khalilian et al, 2016). A meta-analysis by Salpeter et al (2004) reported that beta-2 agonist use in patients with obstructive airway disease increases the risk for cardiovascular adverse events from three days to one year.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 42 potential DDIs found, most of them had moderate (80.95%) and minor (73.80%) severity that is sufficiently to warn us to have a monitoring for the potential dangerous, as shown in Figure 1. (Khalilian et al, 2016). A meta-analysis by Salpeter et al (2004) reported that beta-2 agonist use in patients with obstructive airway disease increases the risk for cardiovascular adverse events from three days to one year.…”
Section: Resultsmentioning
confidence: 99%